Factors that Encourage the Producers to Maintain Local Pig Production in the Subsistence Raising in East Timor - Gomes, Graciano Soares (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
The objective of this study was to evaluate the reasons of producer to maintain the subsistence production system of local pig in East Timor. About 1042 respondents were interviewed in six municipalities and each have been interviewed 10% of total producer’s as respondents, using simple random method to selected the respondents and the interviews based on established questionnaires. The research result showed that about 49.90% of total respondents commented that they still maintain the subsistence production system because the productions costs is very low, and 29.94% of producer’s said that subsistence production system is easy to be use and implement in anywhere. About 12.48% of total respondents commented that the subsistence production system on implementation no needed technical assistance and 7.68% of respondents said that the system is still appropriate with the genetics of local pigs. Besides that, 86.56% of the respondents classified the local pig raising activities as family additional activity. Therefore, it can be concluded that the producers still maintain the system due they are less able to finance these activities if use the modern or intensive production system, and also still consider it a less profitable business among other agricultural activities.